2010
DOI: 10.3390/ijms11114750
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Total Flavonoid Compound Extraction from Gynura medica Leaf Using Response Surface Methodology and Chemical Composition Analysis

Abstract: Optimization of total flavonoid compound (TFC) extraction from Gynura medica leaf was investigated using response surface methodology (RSM) in this paper. The conditions investigated were 30–60% (v/v) ethanol concentration (X1), 85–95 °C extraction temperature (X2) and 30–50 (v/w) liquid-to-solid ratio (X3). Statistical analysis of the experiments indicated that temperature and liquid-to-solid ratio significantly affected TFC extraction (p < 0.01). The Box-Behnken experiment design showed that polynomial regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 29 publications
2
43
0
3
Order By: Relevance
“…Eupatorin dan 3'-hidroksi-5,6,7,4'-tetrametoksiflavon (TMF) diketahui memiliki aktivitas antioksidan yang relatif sama dengan butylated hydroxylanisole (BHA) sedangkan aktivitas antioksidan sinensitin lebih rendah dari BHA pada konsentrasi yang sama (0,05 mg/mL) (Akowuah et al, 2005 Aktivitas antioksidan oleh flavonoid dan senyawa fenol lainnya sebagian besar disebabkan oleh gugus hidroksil aromatik sehingga radikal fenolik menjadi lebih stabil langsung setelah radikal terbentuk ketika satu hidrogen radikal didonorkan ke DPPH (de Souza et al, 2013). Semakin banyak gugus hidroksi pada struktur kimia semakin tinggi aktivitas antioksidan oleh senyawa tersebut (Liu et al, 2010). Sebaliknya, flavonoid yang disubtitusi dengan sejumlah metoksi menunjukkan penurunan aktivitas antioksidan (Jeong et al, 2007).…”
Section: Penanda Senyawa Antioksidanunclassified
“…Eupatorin dan 3'-hidroksi-5,6,7,4'-tetrametoksiflavon (TMF) diketahui memiliki aktivitas antioksidan yang relatif sama dengan butylated hydroxylanisole (BHA) sedangkan aktivitas antioksidan sinensitin lebih rendah dari BHA pada konsentrasi yang sama (0,05 mg/mL) (Akowuah et al, 2005 Aktivitas antioksidan oleh flavonoid dan senyawa fenol lainnya sebagian besar disebabkan oleh gugus hidroksil aromatik sehingga radikal fenolik menjadi lebih stabil langsung setelah radikal terbentuk ketika satu hidrogen radikal didonorkan ke DPPH (de Souza et al, 2013). Semakin banyak gugus hidroksi pada struktur kimia semakin tinggi aktivitas antioksidan oleh senyawa tersebut (Liu et al, 2010). Sebaliknya, flavonoid yang disubtitusi dengan sejumlah metoksi menunjukkan penurunan aktivitas antioksidan (Jeong et al, 2007).…”
Section: Penanda Senyawa Antioksidanunclassified
“…Response surface methodology (RSM) is a statistical method that is useful for mathematical modeling and simultaneously solving multivariate equation (Liu et al, 2010). In the present study, ultrasound-assisted extraction for PCS was investigated and the operational conditions were optimized using BoxBehnken Design (BBD) combined with RSM.…”
Section: Introductionmentioning
confidence: 99%
“…Pharm Sci Asia 2017; 44 (3), [154][155][156][157][158][159][160][161] techniques are collected for designing experiments, building models, evaluating the effects of factors and searching optimum condition of factors for desirable responses 9 .It has been successfully reported that RSM using Box-Behnken design can be used to optimize the extraction conditions from plants to obtain active compounds 9,12 . No such study has been carried out on the extraction of antioxidants from P. barbata leaves.…”
Section: Original Articlementioning
confidence: 99%
“…The efficiency of the extraction of antioxidants from plant source is influenced by multiple parameters such as extraction temperature, time and the liquid-tosolid ratio, among others, and their effects may be either independent or inter-active. In order to overcome this problem, when many factors affect desired variables, response surface methodology (RSM) is an effective tool for optimizing the process [9][10][11] . In RSM, mathematical and statistical *Corresponding author: piyanuch.roj@mahidol.ac.th…”
Section: Introductionmentioning
confidence: 99%